Parque Nacional Islas de Santa Fe - FRASSÓN, PAULA; MANZIONE, MAURICIO; LIER , GUILLERMO (Revista Aves Argentinas, 2025)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número)